Parameter Estimation of Inverse Rayleigh Distribution under Competing Risk Model for Masked data - Panwar, M.S.; Sudhir, Bapat Akanshya; Bundel, Rashmi; Tomer, Sanjeev K. (Journal of Institute of Science and Technology, 2015)
This paper tries to derive maximum likelihood estimators (MLEs) for the parameters of the inverse Rayleigh distribution (IRD) when the observed data is masked. MLEs, asymptotic confidence intervals (ACIs) and boot-p confidence intervals (boot-p CIs) for the lifetime parameters have been discussed. The simulation illustrations provided that as the sample size increases the estimated value approaches to the true value, and the mean square error decreases with the increase in sample size, and mean square error increases with increase in level of masking, the ACIs are always symmetric and the boot-p CIs approaches to symmetry as the sample size increases whereas the mean life time due to the local spread of the disease is less than that due to the metastasis spread in case of real data set. Journal of Institute of Science and Technology, 2015, 20(2): 122-127